(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
The Social Worker, between Values and Difficulties. The values in social work are an amount of desires, needs, personal aspirations, combined with everything that the communities have a right to own, likewise respect, freedom, solidarity, somebody to lean on when life gets too hard to handle on their own. The Code of Ethics represents the mirror of the professional life of any social worker, translated into rules, a guide coming in help for the caseworkers, in order to make the right decisions. Principles like engagement with clients, autonomy, transparency, solidarity, integrity, respect, are based on values with the purpose of protecting the fragile human beings. The social worker as a whole has responsibilities that are tremendous, and whenever stressful situations occur, like not having the possibility to use the proper tools in order to give the adequate form of support, can put a lot of weight on their shoulders, weight that can collapse. Freudenberger was the first psychologist who gave the name to the syndrome of exhaustion caused by the too high volume of work, called burnout. The personality of the person that is a caregiver is characterized by a strong personal motivation and a system of high expectations for impact, personal well-being, efforts and energy to help others. However, when the investment-earning relationship becomes deficient, due to the psychophysical wear and tear that entails „taking care of others”, a series of negative emQotions appear, sometimes accompanied by somatic correlations. In our country, the burnout syndrome is being studied on the medical stuff, definitely one of the most important occupations, but research on the social workers is essential, aimed for the protection of them. Even though caregivers are the ones that protect the vulnerable people, they need protection themselves in order to be able to do their job.